Violence, power, and society in the Dead Sea Scrolls - Jassen, Alex P. (Cambridge University Press, 2025)
"Violence is one of the key themes in the Dead Sea Scrolls. In this volume, Alex P. Jassen explores the intersection of violence and power in the Dead Sea Scrolls and the ancient sectarian movement which generated and preserved these texts. He offers insights into the origins and function of violence for the people behind the Dead Sea Scrolls"-- Provided by publisher